Effect of GPG Program on Improve Pregnancy Rates During Anestrus Period of Dairy Cows in Syria (Journal of Hama University, 2022)
This research aims to study the effect of hormonal treatment on the postpartum period, by using a hormonal program called GPG. In this study, 30 heads of dairy cows were used, which had given birth at least once their ages ranged between (3-5) years, which gave birth at least 80 days ago, without any reproductive disorders (normal uterus-normal ovaries). The cows were randomly divided into three groups. The First, group (G1)(n=10): was treated with GPG program (GnRH  50 mcg in day (0) - PGF2α 150 mcg in day (7) - GnRH 50 mcg in day (9) im) then an artificial insemination was performed 16 hours after the end of the hormonal treatment, regardless of estrus signs. The second group (G2) (n=10): was treated as in the first group, but  was artificially inseminated twice (16 and 24 hours after the end of the hormonal treatment). third group (G3)(Control)(n=10): were treated with a physiological solution at the same time intervals as the three injections used in the experimental groups, and then an artificial insemination was performed 12 hours after the appearance of estrus signs Ultrasound scan was performed on day 35 after AI in all inseminated cows to diagnose pregnancy. The results showed that there was a significant difference (P≤0.05) between (G1-G2) groups and the control group (G3) regarding the rates of estrus emergence, while no significant difference was observed between (G1and G2) groups immediately after the treatment. The results also showed a significant difference (P≤0.05) between (G1-G2-G3) groups regarding pregnancy rates, as the highest pregnancy rate was recorded in the (G2) group immediately after the treatment and also cumulatively. The results also showed that Insemination index in the two experimental groups (G1-G2) reached (1.4-1.28),respectively, as this number was considered to be a good fertility indicator. It was concluded from this study the importance of administration of GPG program to improve and to increase pregnancy rates  in cows during anestrus period due to repeated insemination after the end of hormonal treatment as observed in the second group.
Keywords: Anestrus; GPG; Dairy Cows